(5+3i)(6-3i)=

Simple and best practice solution for (5+3i)(6-3i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5+3i)(6-3i)= equation:


Simplifying
(5 + 3i)(6 + -3i) = 0

Multiply (5 + 3i) * (6 + -3i)
(5(6 + -3i) + 3i * (6 + -3i)) = 0
((6 * 5 + -3i * 5) + 3i * (6 + -3i)) = 0
((30 + -15i) + 3i * (6 + -3i)) = 0
(30 + -15i + (6 * 3i + -3i * 3i)) = 0
(30 + -15i + (18i + -9i2)) = 0

Combine like terms: -15i + 18i = 3i
(30 + 3i + -9i2) = 0

Solving
30 + 3i + -9i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '3'.
3(10 + i + -3i2) = 0

Factor a trinomial.
3((2 + -1i)(5 + 3i)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(2 + -1i)' equal to zero and attempt to solve: Simplifying 2 + -1i = 0 Solving 2 + -1i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1i = 0 + -2 -1i = 0 + -2 Combine like terms: 0 + -2 = -2 -1i = -2 Divide each side by '-1'. i = 2 Simplifying i = 2

Subproblem 2

Set the factor '(5 + 3i)' equal to zero and attempt to solve: Simplifying 5 + 3i = 0 Solving 5 + 3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3i = 0 + -5 3i = 0 + -5 Combine like terms: 0 + -5 = -5 3i = -5 Divide each side by '3'. i = -1.666666667 Simplifying i = -1.666666667

Solution

i = {2, -1.666666667}

See similar equations:

| 10x+8y=4800 | | 8p-57=9p+10 | | 120=.8x | | -4x^2+29x-25=0 | | (sec^2)(x)=7 | | 47-12=5(x-2) | | x^3-3y^3-9z^3=0 | | x+3.5x=90 | | 1566=29(p+20) | | x+x+15+x+75=180 | | 14x=11x+33 | | x+18+3x=-20-3x-25 | | 14x=11x+34 | | 14x=11x+36 | | 14x=11x+41 | | 14x=11x+61 | | -1/5b-2/5=-3 | | 11x=3y-3 | | x^2-6x=135 | | 12t^2-18t+7=0 | | 14x=11x+81 | | 180=x+(2x)+(x-20) | | 23-48=3(x-1)-4 | | 10x/11 | | f(-2)=3x^2+7x-12 | | y-2=x^2-3x+7 | | B/14-b/22 | | 5(2x+10)+1= | | au^2+bu+c=0 | | cosine(2x)+7sin+3=0 | | f(7)=3x^2+7x-12 | | 38-n=-8(1+3n) |

Equations solver categories